Psychological Flexibility and Mindfulness as Predictors of Individual Outcomes in Hospital Health Workers - Ramaci, Tiziana; Bellini, Diego; Presti, Giovambattista; Santisi, Giuseppe (Frontiers in Psychology, 2019)
Research in organizational psychology emphasizes the idea that wellbeing and productivity outcomes are influenced both by individual differences (traits, values) and work environment characteristics (relationships, climate). Evidence for the effectiveness of psychological interventions for stress is currently unclear. To date, research on psychological flexibility in workplaces has not been systematically conducted in Italy. We investigated its relevance in the context of the Italian health care system. In this study, the relationship between sources of stress at work and its outcomes in terms of psychological and physical health are explored. Furthermore, the moderating effect of psychological flexibility and mindfulness on psychological and physical health are investigated. Four hundred and eleven health workers of a Sicilian hospital with different job positions were recruited, of which 42.7% were males (N= 169) and 57.3% were females (N=227). Their ages ranged between 25 and 72 years (M=49.16; SD=8.65). Participants answered a questionnaire that assessed psychological flexibility, mindfulness, sources of stress at work and health benefits. In a bivariate analysis, managerial factors, relationships, and intrinsic factors are partially negatively related to psychological and physical health; whereas, multivariate analyses show that psychological flexibility does not moderate the relationship between psychological and physical health. Instead, mindfulness is strongly and consistently correlated to psychological and physical health. Employees who show psychological flexibility, are more likely to show greater openness to the acceptance of setbacks in the working environment and to carry on their valued living and working path. This seems to correlate positively on individual wellbeing. Data show that a flexible and mindful attitude towards difficult psychological events aids responsiveness to changes and the ability to work more effectively.